Insulin-like peptide 3 (INSL3) is a major regulator of female reproductive physiology - Anand-Ivell, Ravinder; Ivell, Richard (Oxford University Press, 2018)
BACKGROUND: Insulin-like peptide 3 (INSL3) is a member of the relaxin family of neohormones which has evolved to address specifically mammalian aspects of reproduction related to viviparity and internal fertilization. It was originally identified as a major product of testicular Leydig cells and has proved to be an important biomarker of Leydig cell functional capacity. However, INSL3 is also produced by theca interna cells of growing antral follicles and is secreted into the bloodstream in phases corresponding to the number and health of the follicles. Moreover, gene silencing experiments have shown that INSL3 is essentially required for androstenedione synthesis, which is the major steroid precursor for the granulosa cells of antral follicles to produce oestrogens. Knockout studies in mice confirm that loss of INSL3 or its receptor in females leads to partial infertility, with reduced follicle numbers, ovulations and litter size. Circulating INSL3 concentration corresponds to the reproductive lifespan, beginning with puberty and declining at the menopause, and thus may contribute to the physiology of other organ systems, particularly those relevant for hormone replacement strategies.